Optimal placement of distributed generation units in power grid - Muhammad Firdaus Bin Rosli (2023)
The objectives of this research are to locate the optimal placement of distributed generation units in the power system network and to analyze the impact of DG on voltage profile and power losses. The method used in this research is by modeling the IEEE 14-bus system with and without the distributed generation units. To accomplish the research objectives, the network system will be modeled in software known as Power System Simulator for Engineering (PSSE). Then, power flow analysis will be conducted in the PSSE software. The simulation result will be discussed and analyzed using two technical objectives which are voltage profile improvement and power system loss reduction. There are four cases conducted in this paper.